More than Needle and Thread: Inuit Knowledge Sharing and Well-being through Community-based Programs. - Greene, Ezra Anton; Zawadski, Krista Ulujuk (American Review of Canadian Studies, 2022)
Community-based educational programs coordinated and run by local residents, Inuit organizations, and nonprofit organizations are periodically offered in communities in Nunavut. This article presents examples of these programs from the communities of Kangiqłiniq (Rankin Inlet) and Igluligaarjuk (Chesterfield Inlet) as well as programs connecting Inuit with belongings in museum collections held outside of Nunavut. The research involved anthropological methods of participant observation, interviews, and ethnographic insights from experiences of organizing and participating in programs. Indigenous research methodologies also guide the research. We elaborate how community-based programs provide opportunities for Inuit knowledge generation and transmission while contributing to well-being and community cohesion. These programs can (re)connect and engage Inuit with knowledge of the land, traditional and contemporary cultural practices, and Inuit belongings that have been disconnected from communities and individuals through colonial processes.